Psycho-sexual Disorders in Clinic Diabetes mellitus Patients of a Teaching Hospital of Eastern Nepal - Shakya, Dhana Ratna; Maskey, R; Karki, P; Sharma, SK (Journal of Diabetes and Endocrinology Association of Nepal, 2020)
Background: Diabetes mellitus, a chronic disease, is frequently associated with sexual dysfunctions. Identification and management of these dysfunctions are important for overall wellbeing of the patient, though usually neglected. We lack data on this regard from Nepal.Objective: To estimate prevalence of psycho-sexual disorders (with emphasis on erectile dysfunction) in the patients with diabetes mellitus visiting ‘Diabetes clinic’ of a tertiary care teaching hospital in eastern Nepal.Method: It is a hospital-clinic based prevalence study. This study analyzed consecutive diabetes mellitus clinic patients’ response to self response questionnaires ‘Arizona Sexual Experience Scale’ (ASEX) for over all sexual dysfunction and ‘5- Item Version of the International Index of Erectile Dysfunction’ (IIEF-5) for erectile dysfunction. ‘Diabetes mellitus’ diagnosis was made based on the ADA guidelines 2010.Results: Among 100 male clinic diabetes patients, majorities were married, above age 50 years and all diagnosed as type 2 diabetes mellitus. Out of total, 48% had sexual dysfunction by the ASEX and many subjects had erectile dysfunction by the IIEF-5.Conclusion: Psychosexual dysfunctions, mainly erectile dysfunction are common among diabetic patients. Hence, assessment should include attention to sexual problems as well during management of diabetes mellitus.